2006
DOI: 10.1111/j.1440-1819.2006.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐month use of mental health services in four areas in Japan: Findings from the World Mental Health Japan Survey 2002–2003

Abstract: The aim of the present study was to provide basic descriptive data regarding utilization of 12-month mental health services in the Japanese community population. Face-to-face household surveys were carried out in four areas (two urban cities and two rural municipalities), and a total of 1663 persons participated (overall response rate: 56.4%). For data collection, the structured psychiatric interview, World Mental Health version of the World Health Organization Composite International Diagnostic Interview (WMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 21 publications
2
40
1
Order By: Relevance
“…The present findings may be largely influenced by help-seeking behaviours due to depressive disorders, which were underdiagnosed in many countries. In Japan, the 12-month medical treatment rate for depressive disorders was reported as only 27%, which was much lower than those in the US and some European countries,49 possibly because of a greater stigma towards depressive disorders in Japan 50. A substantial proportion of workers who had depressive disorders may have not gone on long-term sick leave, or even when they went on sickness absence, their sickness absence may not have been diagnosed as depressive disorders.…”
Section: Discussionmentioning
confidence: 93%
“…The present findings may be largely influenced by help-seeking behaviours due to depressive disorders, which were underdiagnosed in many countries. In Japan, the 12-month medical treatment rate for depressive disorders was reported as only 27%, which was much lower than those in the US and some European countries,49 possibly because of a greater stigma towards depressive disorders in Japan 50. A substantial proportion of workers who had depressive disorders may have not gone on long-term sick leave, or even when they went on sickness absence, their sickness absence may not have been diagnosed as depressive disorders.…”
Section: Discussionmentioning
confidence: 93%
“…In rural areas, most patients consult a general internist who plays a role similar to that of a primary care physician in the UK. It has been reported that depressed patients in Japanese communities tend to consult not only mental health specialists, but also other specialists such as a general internists because of their somatization in addition to the stigmatization of psychiatric disorders and services [6,7]. The importance of primary care provided by general internists in the management of depressed patients has been stated recently in the Comprehensive Suicide Prevention Initiative published by the Japanese Government.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Informed consent was obtained before beginning the interviews. The Human Subjects Committees of Okayama University (for the Okayama site), Japan NIMH (for the Kagoshima site), and Nagasaki University (for the Nagasaki site) approved the recruitment, consent, and field procedures.…”
Section: Methodsmentioning
confidence: 99%